(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Small businesses are the backbone of many economies, yet they face numerous challenges in terms of sustainability, growth, and competition. Effective management strategies are essential for these businesses to remain competitive and successful. This paper explores key strategies that can be implemented to improve the management of small business enterprises. The study identifies strategic areas such as leadership, financial management, marketing, innovation, and human resource management that require improvement for business growth. Additionally, the research discusses the role of technology and digital tools in enhancing business operations. Based on various case studies and academic literature, the paper provides actionable recommendations for small business owners and managers to adopt and tailor management strategies that best fit their business needs.